An experimental model of acute pulmonary damage induced by the phospholipase A2-rich venom of the snake Pseudechis papuanus - Solano Centeno, Daniela (2025)
An experimental model of acute pulmonary damage was developed based on the intravenous injection of the phospholipase A2 (PLA2)-rich venom of Pseudechis papuanus (Papuan black snake) in mice. Venom caused pulmonary edema, with the accumulation of a protein-rich exudate, as observed histologically and by analysis of bronchoalveolar lavage fluid (BALF). In parallel, venom induced an increase in all of the pulmonary mechanical parameters evaluated, without causing major effects in terms of tracheal and bronchial reactivity. These effects were abrogated by incubating the venom with the PLA2 inhibitor varespladib, indicating that this hydrolytic enzyme is responsible for these alterations. The venom was cytotoxic to endothelial cells in culture, hydrolyzed phospholipids of a pulmonary surfactant, and reduced the activity of angiotensin-converting enzyme in the lungs. The pretreatment of mice with the nitric oxide synthase inhibitor L-NAME reduced the protein concentration in the BALF, whereas no effect was observed when mice were pretreated with inhibitors of cyclooxygenase (COX), tumor necrosis factor-α (TNF-α), bradykinin, or neutrophils. Based on these findings, it is proposed that the rapid pathological effect of this venom in the lungs is mediated by (a) the direct cytotoxicity of venom PLA2 on cells of the capillary–alveolar barrier, (b) the degradation of surfactant factor by PLA2, (c) the deleterious action of nitric oxide in pulmonary tissue, and (d) the cytotoxic action of free hemoglobin that accumulates in the lungs as a consequence of venom-induced intravascular hemolysis. Our findings offer clues on the mechanisms of pathophysiological alterations induced by PLA2s in a variety of pulmonary diseases, including acute respiratory distress syndrome (ARDS).